Effect of Cash Ratio and Debt to Asset Ratio on Net Profit Margin at PT. Indocement Tunggal Prakarsa Tbk - Sri Sugiarti; Nadia Ulfa Nasution (Kusuma Negara Business School, 2021)
Cash is part of the liquidity ratio which is liquid which is commonly used in companies in carrying out their activities, debt is an obligation that must be paid by a company where debt is part of the solvency ratio and profit is the result of sales obtained by the company where this ratio is part of the profitability ratio. The independent variable used in this study is the Cash Ratio which is able to measure the availability of cash owned by the company to pay its current debts and the Debt to Asset Ratio to measure the amount of assets owned by the company in paying its debts, while the dependent variable is the Net Profit Margin used To calculate the net profit generated by the company on sales made by the company, the formulation of the problem formulated is the effect of the Cash Ratio and Debt to Asset Ratio on the Net Profit Margin. The methodology used is using SPSS version 22. With the results obtained that the correlation value is 0.980 where this number is close to 1, which means that there is a strong correlation between the variables, from the coefficient of determination which gives an effect of 93.4% and the rest influenced by other variables, and from the calculated F value of 36.251 with a significant value of 0.05 and F table of 6.944 which shows the calculated F value is greater than F table which means Ho is rejected and Ha is accepted which means that the Cash Ratio and Debt to Asset Ratio simultaneously have a significant influence on the Net Profit Margin.